Epitope Mapping of trans-Sialidase from Trypanosoma cruzi Reveals the Presence of Several Cross-Reactive Determinants - Pitcovsky, Tamara A. (American Society for Microbiology, 2001)
Trypanosoma cruzi, the agent of Chagas' disease, expresses trans-sialidase, a unique enzyme activity that enables the parasite to invade host cells by transferring sialyl residues from host glyconjugates to the parasite's surface acceptor molecules. The enzyme is also shed into the surrounding environment, causing apoptosis in cells from the immune system. During infections, an antibody response against the catalytic region of the trans-sialidase that is coincident with the control of the parasitemia and survival of the host is observed. This low-titer humoral response is characterized by its persistence for many years in benznidazole-treated patients. Here we analyzed the antigenic structure of the molecule by phage-displayed peptide combinatorial libraries and SPOT synthesis. Several epitopes were defined and located on the three-dimensional model of the enzyme. Unexpectedly, cross-reaction was found among several epitopes distributed in different locations displaying nonconsensus sequences. This finding was confirmed by the reactivity of three monoclonal antibodies able to recognize non-sequence-related peptides that together constitute the surface surrounding the catalytic site of the enzyme. The presence of cross-reacting epitopes within a single molecule suggests a mechanism developed to avoid a strong humoral response by displaying an undefined target to the immune system.